Practice Trends in the Use of Extracorporeal Treatments for Poisoning in Four Countries. Issue 1 (9th November 2015) - Ghannoum, Marc; Lavergne, Valery; Gosselin, Sophie; Mowry, James B.; Hoegberg, Lotte C. G.; Yarema, Mark; Thompson, Margaret; Murphy, Nancy; Thompson, John; Purssell, Roy; Hoffman, Robert S.
Abstract: Extracorporeal treatments (ECTRs) such as hemodialysis (HD), enhance the elimination of a small number of toxins. Changes in overdose trends, prescribing practices, antidotes, and dialysis techniques may alter the indications and rates of ECTR use over time. This study analyzed trends in ECTR for poisonings in four countries. A retrospective study of national poison center databases from the United States, Denmark, United Kingdom, and five regional databases within Canada was performed. All cases of patients receiving an ECTR were included. ECTR cases were totalled annually and reported as annual rates per 100, 000 exposures with stratification per types of ECTR and toxins. The data collection varied by countries. United States, 1985–2014; United Kingdom, 2011–2013; Denmark, 2005–2014, and regions of Canada as follows: Alberta, 1991–2015; Saskatchewan, 2001–2015; Nova Scotia‐PEI, 2006–2015; Quebec, 2008–2014; Ontario‐Manitoba, 2009–2015; British Columbia, 2012–2015. During the study period, the total number of ECTRs and rates per 100, 000 exposures, respectively, were: United States, 40, 258 and 65.7; United Kingdom, 343 and 232.6; Denmark, 616 and 305.5; Canada, 2709 and 177.5; case rates increased over time for the United States, Denmark, and Canada, but decreased in the United Kingdom. Across the United States and Denmark, HD was the preferred modality used. Toxins for which ECTR was most often used were: United States, ethylene glycol; Canada, methanol; United Kingdom, ethylene glycol; Denmark, salicylates. A high number of ECTRs were performed for atypical toxins such as acetaminophen and benzodiazepines. These data demonstrate a growing use of HD for poisoning with significant regional variations in the overall rates and indications.